Duration and mode of delivery: Does maternal sleep matter? - Parttimaa, Hilla; Paavonen, E. Juulia; Perasto, Laura; Karlsson, Hasse; Karlsson, Linnea; Polo‐Kantola, Päivi (John Wiley & Sons, 2026)
Objective
Poor sleep quality in late pregnancy has been identified as a risk factor for operative deliveries. In this study, we investigated the associations between maternal sleep throughout pregnancy and its impact on both the duration and mode of delivery.
Methods
We enrolled 3141 mothers and assessed sleep at four time points during pregnancy (early, mid-, and late pregnancy, and at delivery) using the Basic Nordic Sleep Questionnaire. Delivery data were obtained from the Finnish Birth Registry. Both longitudinal and cross-sectional analyses were performed, adjusting for confounding factors.
Results
In mid-pregnancy, poor sleep quality was associated with a longer first stage (436 vs. 399 min, P = 0.027) and overall duration of delivery (468 vs. 431 min, P = 0.034). In late pregnancy, short sleep duration (<6 h) (adjusted odds ratio [aOR] 2.57, 95% confidence interval [CI]: 1.15–5.72, P = 0.021) and poor sleep quality (aOR 1.68, 95% CI: 1.17–2.41, P = 0.005) were linked to an increased likelihood of unplanned cesarean section. Poor sleep quality (aOR 2.60, 95% CI: 1.52–4.46, P < 0.001) and frequent nocturnal awakenings (aOR 1.72, 95% CI: 1.01–2.89, P = 0.042) were associated with planned cesarean section, while habitual awakenings also increased the risk of vacuum extraction (aOR 1.45, 95% CI: 1.07–1.96, P = 0.018). At delivery, poor sleep quality remained associated with planned cesarean section (aOR 1.99, 95% CI: 1.04–3.82, P = 0.037). In longitudinal analyses, persistent insomnia and sleepiness were not associated with duration or mode of delivery.
Conclusion
Maternal sleep is associated with the mode, but not with the duration of the delivery. Poor and short sleep during late pregnancy is related to instrumental deliveries.